2018
DOI: 10.1002/2017jg004361
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impacts on Net Ecosystem Productivity in a Subtropical Shrubland of Northwestern México

Abstract: The sensitivity of semiarid ecosystems to climate change is not well understood due to competing effects of soil and plant‐mediated carbon fluxes. Limited observations of net ecosystem productivity (NEP) under rising air temperature and CO2 and altered precipitation regimes also hinder climate change assessments. A promising avenue for addressing this challenge is through the application of numerical models. In this work, we combine a mechanistic ecohydrological model and a soil carbon model to simulate soil a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 182 publications
(279 reference statements)
0
20
0
2
Order By: Relevance
“…In contrast, the parking lot at PL exhibited a very small increase in CO 2 emissions (higher FC) after rainfall events during the early summer that was Carbon dioxide fluxes in Phoenix, Arizona also noted at REF ( Fig 10B), but not at a significant level (mm byt m = 0.33). This suggests that additional water from precipitation during a period of high temperatures in May and June promotes CO 2 efflux, mainly by increasing soil respiration in bare soil areas, in a similar fashion as noted in natural ecosystems of the region [90,91,99,100]. During other times of the year, the site with ample outdoor water use (ML) does not respond to precipitation (FC remains the same), suggesting that a decoupling occurs between CO 2 fluxes and storm inputs as commonly found in mesic regions.…”
Section: Sensitivity To Precipitation and Urban Irrigationmentioning
confidence: 55%
“…In contrast, the parking lot at PL exhibited a very small increase in CO 2 emissions (higher FC) after rainfall events during the early summer that was Carbon dioxide fluxes in Phoenix, Arizona also noted at REF ( Fig 10B), but not at a significant level (mm byt m = 0.33). This suggests that additional water from precipitation during a period of high temperatures in May and June promotes CO 2 efflux, mainly by increasing soil respiration in bare soil areas, in a similar fashion as noted in natural ecosystems of the region [90,91,99,100]. During other times of the year, the site with ample outdoor water use (ML) does not respond to precipitation (FC remains the same), suggesting that a decoupling occurs between CO 2 fluxes and storm inputs as commonly found in mesic regions.…”
Section: Sensitivity To Precipitation and Urban Irrigationmentioning
confidence: 55%
“…While groundwater connections are unknown, it was clear that monsoon rainfall patterns were an important driver of wetland area in monsoonal watersheds. Analysis of future climate in the Mexican Highlands predicts precipitation from 2030 to 2045 to be variable, but remains similar to patterns of recent decades (Verduzco et al, 2018). Although Cook and Seager (2013) similarly found that by 2080-2099 total precipitation would remain approximately the same, the timing of peak monsoon rainfall would shift from June-July to September-October.…”
Section: Implications To Waterbird Conservationmentioning
confidence: 87%
“…The study site is a subtropical shrubland near the town of Rayón, Sonora at coordinates 110.53º W and 29.74º N at ~630 m asl., and is part of the MexFlux network (Vargas et al, 2013;Villareal et al, 2016). The climate of the region is semi-arid, BSh according to Köppen's Classification (Verduzco et al 2018). (Watts et al, 2007), which brings about 60% of the annual precipitation.…”
Section: Study Locationmentioning
confidence: 99%
“…For this reason, most of the species at the site lose their leaves in the dry season (from October to June) and recover their greenness in late June or early July. Several hydrological and eco-hydrological studies have been conducted in this site (Tarin et al, 2014;Vivoni et al, 2010;Mendez-Barrozo et al, 2014;Verduzco et al, 2018).…”
Section: Study Locationmentioning
confidence: 99%